Penggunaan Metode Analytic Hierarchy Process (AHP) Dalam Sistem Pendukung Keputusan Kelulusan Penerimaan Mahasiswa Baru Di Sekolah Tinggi Teknologi Pagar Alam - Siti Aminah (JURNAL ILMIAH BETRIK : Besemah Teknologi Informasi dan Komputer, 2020)
Analitycal Hierarchy Process (AHP) method is a general theory of intelligent application that is used for complex mathematical approaches, but based on a qualitative approach that is acceptable to all stakeholders and program managers. Decision Support System can be used by embedding the AHP method in the decision support system on the admission of new students. In the process of admitting new students of the Pagar Alam College of Technology, the selection system is used with several criteria to determine the competency of prospective students. Selection of prospective students has so far been using manual calculations, namely by accumulating test results in accordance with predetermined criteria, a long and complicated process because the number of participants registering can lead to a draw value between prospective students, therefore, to minimize miscalculations of selection results new students and facilitate ranking made a new student graduation test decision support system. The method used to support this research is the waterfall, with 5 stages in accordance with the research conducted. From the method carried out, this study produced a decision support system to determine the graduation of new students in the admission process.